1978
DOI: 10.1017/s0140525x00075506
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal expectancy effects: the first 345 studies

Abstract: The research area of interpersonal expectancy effects originally derived from a general consideration of the effects of experimenters on the results of their research. One of these is the expectancy effect, the tendency for experimenters to obtain results they expect, not simply because they have correctly anticipated nature's response but rather because they have helped to shape that response through their expectations. When behavioral researchers expect certain results from their human (or animal) subjects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
468
2
18

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,010 publications
(513 citation statements)
references
References 56 publications
(70 reference statements)
25
468
2
18
Order By: Relevance
“…Thus, providers might have behaved more expressively toward clients for whom they had more positive expectations. Interpersonal expectations are often subtly and nonconsciously communicated through nonverbal behavior (Rosenthal, 1987;Rosenthal & Rubin, 1978). Given these results regarding the relationship between physical therapists' behavior, especially distancing behavior, and elderly clients' health outcome, we became interested in further examining one potential mechanism underlying the relationship between therapist behaviors and client health outcome: client perception.…”
Section: Physical Therapists' Molecular Nonverbal Behavior As Predictmentioning
confidence: 99%
“…Thus, providers might have behaved more expressively toward clients for whom they had more positive expectations. Interpersonal expectations are often subtly and nonconsciously communicated through nonverbal behavior (Rosenthal, 1987;Rosenthal & Rubin, 1978). Given these results regarding the relationship between physical therapists' behavior, especially distancing behavior, and elderly clients' health outcome, we became interested in further examining one potential mechanism underlying the relationship between therapist behaviors and client health outcome: client perception.…”
Section: Physical Therapists' Molecular Nonverbal Behavior As Predictmentioning
confidence: 99%
“…The study is criticised for numerous methodological errors and expressing in the report opinions that are consistent with popular beliefs concerning teachers' lack of competencies (Snow 1995;Spitz 1999;Wineburg 1987). Finally, in a series of meta-analyses summarising the results of subsequent studies verifying the Pygmalion hypothesis, it was demonstrated that expectancy effects are a real phenomenon affecting educational outcomes of a large group of students (Harris and Rosenthal 1985;Rosenthal 1997;Rosenthal and Rubin 1978). In one of the last meta-analyses, based on the results of 674 studies, Hattie (2008) established that the size of teacher expectancy effect is d = 0.43.…”
Section: Introductionmentioning
confidence: 99%
“…Los precursores en el estudio acerca de la influencia que tienen las expectativas de unas personas sobre otras fueron (Rosenthal y Rubin, 1978).…”
Section: Aproximación Teóricaunclassified